Biosynthesis of Silver Nanoparticles from Protium serratum and Investigation of their Potential Impacts on Food Safety and Control - Mohanta, Yugal K.; Panda, Sujogya K.; Bastia, Akshaya K.; Mohanta, Tapan K. (Frontiers in Microbiology, 2017)
Silver nanoparticles play an integral part in the evolution of new antimicrobials against the broad ranges of pathogenic microorganisms. Recently, biological synthesis of metal nanoparticles using plant extracts has been successfully consummated. In the present study, the biosynthesis of silver nanoparticles (AgNPs) was conducted using the leaf extract of plant Protium serratum, having novel ethnomedicinal. The synthesized AgNPs were characterized using UV-Visible spectroscopy, dynamic light scattering spectroscopy (DLS), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The DLS study revealed the surface charge of the resulted nanoparticles that was highly negative i.e. -25.0 ± 7.84 mV and the size was 74.56 ± 0.46 nm. The phytochemical and FTIR analysis confirmed the role of water-soluble phyto-compounds for the reduction of silver ions to silver nanoparticles. The potential antibacterial activity of AgNPs was studied against the food borne pathogens viz. Pseudomonas aeruginosa (IC50=74.26±0.14µg/ml), Escherichia coli (IC50= 84.28±0.36µg/ml) and Bacillus subtilis (IC50=94.43±0.4236µg/ml). The in vitro antioxidant potential of AgNPs was evaluated using 1, 1-diphenyl-2-picryl-hydrazil (DPPH) (IC50=6.78±0.15 µg/ml) and hydroxyl radical assay (IC50=89.58±1.15 µg/ml). In addition, the cytotoxicity of AgNPs was performed against fibroblast cell line L-929 to evaluate their biocompatibility. The overall results of the present investigation displayed the potential use of Protium serratum leaf extract as a good bio-resource for the biosynthesis of AgNPs and their implementation in diverse applications, specifically as antibacterial agent in food packaging and preservation to combat against various food borne pathogenic bacteria along with its pharmaceutical and biomedical applications.